Synthesis and characterization of nitrogen-functionalized graphene oxide in high-temperature and high-pressure ammonia - Baldovino, Fritzie Hannah B. (Animo Repository, 2016)
A novel and efficient approach to the synthesis of nitrogen-functionalized graphene oxide (GO) using aqueous ammonia, NH3 (aq.), under high-temperature and high-pressure conditions was investigated. Nitrogen groups (N-groups) were incorporated in GO in different ways; by replacing the carbon (C) atoms and reacting with the oxygenated functionalities present in GO. Reaction mechanisms were proposed, showing how N-groups were attached to GO. Functionalization was confirmed using Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), nuclear magnetic resonance (NMR) spectroscopy and elemental analysis (EA). Raman spectroscopy, X-ray diffraction spectroscopy (XRD), and scanning electron microscopy (SEM) were employed to further characterize GO modification. Functionalization was carried out to increase GO adaptability to a wide range of applications, including carbon dioxide (CO2) capture and electrochemical oxygen reduction as reported. © The Royal Society of Chemistry.